Reduplikasi Bahasa Melayu Riau Dialek Belilas Indragiri Hulu - Boni Afreselia; Alber Alber (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2023)
The problem in this study is how is the form of reduplication and the meaning of reduplication contained in the Riau Malay dialect of the Belilas sub-district of the Kasai base, Seberida sub-district, Indragiri Hulu district? The research approach used is a qualitative approach. The research method is qualitative descriptive. Based on the results of data analysis, the author examined the form of reduplication in Riau Malay dialect, Pangkalan Kasai Village, Seberida District, Indragiri Hulu Regency. then the meaning of reduplication, namely expressing the meaning of "many" is found, for example: [sedae-sedae], [baghaŋ-baghaŋ], stating the meaning of 'unconditional', for example: [ujan-ujan], [kociɁ-kociɁ], stating the meaning of 'action in the form The basic form is repeated for example: [meŋomas-ŋomas], [crying-nguwut], Stating the meaning 'the action in its basic form is done comfortably, casually, or with pleasure' for example: [memaɁai-maɁai], [chattering], Stating the meaning of 'actions in the basic form are carried out by two parties regarding each other, namely [bemusiɁ-musiɁ], Stating the meaning of 'things related to work in the basic form', namely [bemasaɁ-masaɁan], Stating the meaning 'intensity of feelings', for example: [ letaɁ-letaɁ], [meadaŋ-adaŋ].